Hubungan Antar Agama pada Masa Kerajaan Usmani - Lukman Hakim (Historia Madania: Jurnal Ilmu Sejarah, 2019)
This paper focuses on the concept of religious tolerance in the Ottoman Empire after the conquest of Constantinople by Sultan Muhammad al-Fatih II. This idea had been known as the millet system. The implementation of the millet system under the Ottoman rule was proof that the Ottoman empire had been able to implement religious and cultural harmony. They lived in harmony to make a peace among religions. This paper also attempts to describe a millet system model that had been running for hundreds of years since this concept was created. Co-existence in religious and cultural diversity has been demonstrated by the Ottoman empire in its multicultural and multireligious society. This paper also shows how the millet system can provide benefits if the authorities provide space for recognition to minority groups or people in the territory. Keyword: Non-Muslim, Millet system, Ottoman, communities.